Seed guide path planning and parameter optimization for air-suction carrot seed-metering device - Wang, Fangyan; Zhang, Wenxin; Jiang, Jingtao (International Journal of Agricultural and Biological Engineering, 2023)
To meet the requirement of "zero speed" for precision sowing, the instantaneous speed of seed falling into the seed bed should be equal to the opposite direction of the forward speed of the machine. Through analyzing the principle of seed guiding process, the main influencing factors affecting the contour curve of the seed tube were determined to plan the seed guiding path and realize zero speed seed delivery. With the help of EDEM simulation software, taking the inclination angle of seed tube end, operating speed of the metering disc, and machine’s forward speed as the experimental factors, a single-factor simulation test was conducted with the pass rate, replay rate, and missing seeding rate as experimental indexes. The results of the simulation test showed that the range of inclination angle of the seed tube end was 23°-40°, the range of machine forward speed was 5-9 km/h, and the range of operating speed of the metering disc was 15-40 r/min. The quadratic orthogonal rotation combination test method was carried out using the bench test, and a mathematical regression model was established between experimental factors and experimental indexes to determine the priority order of factors, and the best combination of factors. The test results showed that the pass rate was 93.25%, the replay rate was 2.97% and the missing seeding rate was 3.78% under the condition with the inclination angle of seed tube end of 32.28°, the forward speed of the machine of 6.89 km/h and the operating speed of the metering disc of 28.67 r/min, which can meet the requirements of relevant national standards.Keywords: carrot, seed-metering device, seed guiding process, mechanism analysis, EDEM software, bench testDOI: 10.25165/j.ijabe.20231605.8210Citation: Wang F Y, Zhang W X, Jiang J T. Seed guide path planning and parameter optimization for air-suction carrot seed-metering device. Int J Agric & Biol Eng, 2023; 16(5): 104–112.